Popular Issues in Islamic Education Management - Daulay, Muhammad Roihan; Pulungan, Husniah Ramadhani (CV. Creative Tugu Pena, 2024)
This research aims to find popular issues in Islamic education management. This is done because a study requires assistance in mapping problems that need to be overcome and improved in the management system so that it becomes better so that it is easier to adapt in its implementation. This research method uses literature study with data taken from the latest journal articles on Google Scholar from 2020 to 2023 only. The results of the research found that there are 10 popular issues in Islamic education management which include (1) the issue of integration of Islamic values, (2) the issue of empowering teachers and teaching staff, (3) the issue of using technology in Islamic education, (4) the issue of resource management power, (5) issues of parent and community participation, (6) issues of curriculum development, (7) issues of character and ethics development, (8) issues of overcoming radicalism and extremism, (9) issues of justice and equality, and (10) issues of performance measurement and evaluation. The novelty of this research found that the most popular issue in Islamic education management is the issue of radicalism and extremism (issue 8) because the discussion is highest during 2023. Thus, issue 8 is an issue that requires a special approach and can be anticipated both internally and externally from every Islamic school in Indonesia. Keywords: Issue Islamic Education Management, Education Management, Popular Issues Management